The Transformation of the Strategy for Internalizing Religious Moderation Values to Strengthen Students’ Nationalist Character - Harmonis, Mistria (Indonesian Journal of Education Research (IJoER), 2025)
Purpose of the study: This article aims to describe and provide an in-depth analysis of the transformation of strategies for internalizing religious moderation values in strengthening students’ nationalist character. The study employed a qualitative approach using a case study design. Methodology: The research was conducted at Madrasah Tsanawiyah Karomatullah Betek Krucil from September 1 to October 30, 2025. Data were collected using the snowball sampling technique, with both primary and secondary data sources.Data collection methods included in-depth interviews, participant observation, and documentation studies.Data analysis was carried out using the Miles and Huberman interactive model, which consists of data reduction, data display, and conclusion drawing. Main Findings: The findings reveal that the internalization of religious moderation to strengthen students’ nationalist character at Madrasah Tsanawiyah Karomatullah Betek Krucil Probolinggo is carried out through the integration of moderation values into Aswaja and Civics education, seminars on religious moderation in national life, the commemoration of Independence Day and National Santri Day, teacher role modeling that reflects moderate and nationalist values, and regular flag-raising ceremonies. Novelty/Originality of this study: The novelty of this study lies in its emphasis on the transformative internalization of religious moderation values as a central mechanism for strengthening students’ nationalist character at Karomatullah Betek Krucil Probolinggo. It advances a conceptual framework explaining students’ cognitive, affective, and behavioral transformation in translating religious moderation values into a sustained nationalist disposition.